Sensorless control of high‐speed BLDC motor using equal area criterion based precise commutation scheme with Fuzzy based phase delay compensation. (11th July 2021) - Soni, Umesh Kumar; Tripathi, Ramesh Kumar
Summary: Sensorless control of BLDC motors is preferred nowadays due to a number of drawbacks in sensor based control. Line‐to‐line back EMF is generally extracted by filtering the terminal voltages. In case of high‐speed operation, the phase delay becomes very large and result in imprecise commutation with large phase currents, high torque ripple, and reduced efficiency. In such case, linear strategy of commutation advancement alone cannot be successful. In this paper, a Fuzzy based phase delay compensation scheme has been proposed. The smooth variation of coefficients of the least P th‐Norm IIR digital filter is achieved using close loop Fuzzy control for operation from low‐ to high‐speed range without commutation precision loss. This enables the increase of filter cut‐off frequency and gain to overcome the phase delay and attenuation at higher speeds. The commutation delays may still be present even after phase delay compensation because of filtering frequency limitation to avoid the effect of spikes occurring due to diode freewheeling. Equal area criterion (EAC) has been proposed for commutation error correction. The required correction in threshold constant is calculated by difference of ripple current integral before and after the valley point. The controller has been developed using MATLAB/Simulink and validated using real‐time windows target NI PCI‐6221 DAQ and 400 W, 12000 rpm brushless spindle motor. Experimental phase delay of 13.6° and commutation error of 2° was achieved after application of EAC at 11250 rpm. The proposed system provides higher efficiency with reduced startup time. Abstract : High efficiency sensorless control of BLDC motors is being preferred day by day due to drawbacks of sensors. Back EMF information is essential for sensorless control and low pass filters are mostly used for it's extraction from terminal voltages. Phase delay, attenuation, and commutation error are major problems at high‐speed operation, which causes imprecise commutation with large phase currents, high torque ripple, and reduced efficiency. In this paper, Fuzzy based close‐loop scheme for compensation of filtering phase delay and attenuation has been proposed. Cut‐off frequency and gain of the least P th‐Norm IIR digital filter are increased using Fuzzy based smooth variation of filter coefficients, as speed increases. Equal area criterion (EAC) has been proposed for commutation error correction applied after Phase delay compensation. Both the schemes have together improved steady state and dynamic performance of system with inmproved efficency and reduced startup time.